Future Directions for Conservation. (August 2016) - Keulartz, Jozef
The use of target baselines or reference states for conservation and restoration has become increasingly problematic and impractical, due to rapid environmental change, the paradigm shift in ecology from a static to a dynamic view of nature, and growing awareness of the role of cultural traditions in the reconstruction of baselines. The various responses to this crisis of baselines will to a significant extent determine the future direction of nature conservation. Although some hold onto traditional baselines and others try to refine or re-define the reference concept, the debate is currently dominated by two widely diverging reactions to the crisis: while the so-called 'new environmentalists' or 'new conservationists' declare the whole baseline notion obsolete, replacing a backward-looking approach with a forward-looking one, the 're-wilders' push the baseline back to a deeper, more distant past. This article provides a critical assessment of the debate on these conversation options, with a special focus on the differences between Old World and New World perspectives.